Test weight affects the milling characteristics of grain sorghum - Traylor, S.L.; Herrman, Timothy J.; Behnke, Keith C.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
As test weight was reduced from normal to intermediate (i.e., from 58 to 52 lb/bu), little change occurred in milling characteristics of grain sorghum. However, as test weight was decreased from intermediate to light (52 to 39 lb/bu), production rate slowed and cost of grinding increased dramatically. Decreasing screen opening size from 8/64 in to 3/64 in also decreased production rates and increased electrical energy costs, with these effects much more pronounced in light test-weight sorghum.
Keywords: Swine; Sorghum; Test weight; Grinding